The Lost Boys Gift - Holt, Kimberly Willis; Bean, Jonathan 1979- (New York Henry Holt and Company, 2019)
When his parents separate, Daniel very unhappily moves to a cottage on While-A-Way Lane, but neighbor Tilda Butter helps him discover he has a special gift like hers.
"Christy Ottaviano Books."
Keywords: Moving, Household -- Fiction; Neighborhoods -- Fiction; Human-Animal communication -- Fiction; Schools -- Fiction; Theater -- Fiction; Family problems -- Fiction